СИСТЕМА КЕРУВАННЯ ЗВОРОТНО-ОБЕРТАЛЬНИМ РУХОМ РОТОРА БЕЗКОНТАКТНОГО МАГНІТОЕЛЕКТРИЧНОГО ДВИГУНА - Акинін, К.П.; Антонов, О.Є.; Кіреєв, В.Г.; Філоменко, А.А. (Інститут електродинаміки Національної академії наук України, 2020)
A subject of this paper is a development of the system of control by return-rotary motion of rotor of brushless magnetoelectric motor. In the paper we studied a method for calculating a control system of the rotation angle amplitude of the rotor shaft by specifying the phase stability margin based on the frequency characteristics of an open-loop system. A calculation of the loop of the current effective value of stator windings is carried out on the basis of a given limitation accuracy. Using the obtained analytical dependences allows us to automatically calculate the controller parameters depending on the frequency of mechanical vibrations of the rotor shaft in a given operating range. In the paper we provide the examples of transient responses for controlling the rotation angle amplitude and current effective value at the motor start and mechanical load changes. Reference 9, figure 5, table 3.